2013
DOI: 10.1155/2013/781029
|View full text |Cite
|
Sign up to set email alerts
|

Apathy and Related Executive Syndromes in Dementia Associated with Parkinson’s Disease and in Alzheimer’s Disease

Abstract: Abstract. Apathy is defined as a lack of motivation and has been reported to be common in Alzheimer's disease (AD) and Parkinson's disease (PD). To explore the neuropsychological correlates of apathy in patients with PD related dementia (PDD) and AD and to identify the specific cognitive profile of apathy in the two forms of neurodegenerative disease, 61 non-depressed patients (29 PDD and 32 AD) were selected. Out of these, 29 patients (47.5%) were detected as apathetic (14 PDD-A+ and 15 AD-A+), and 32 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
6
15
0
Order By: Relevance
“…Additionally, the current study found a significant association between apathy and letter fluency scores, which is also in line with previous findings in more severe patients [4,13,15]. Moreover, a similar pattern of executive dysfunction has been reported in apathetic patients with PD with dementia and apathetic patients with AD [50]. Taken together, the findings of the present study highlight the presence of a strong association between apathy and the presence of executive deficits.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the current study found a significant association between apathy and letter fluency scores, which is also in line with previous findings in more severe patients [4,13,15]. Moreover, a similar pattern of executive dysfunction has been reported in apathetic patients with PD with dementia and apathetic patients with AD [50]. Taken together, the findings of the present study highlight the presence of a strong association between apathy and the presence of executive deficits.…”
Section: Discussionsupporting
confidence: 93%
“…[23]. A similar pattern has been reported in other studies (e.g., 23% depression only, 23% depression + apathy, and 20% apathy only) [66, 67]. This frequent comorbidity suggests shared etiology.…”
Section: Apathysupporting
confidence: 79%
“…An original research paper by Grossi et al in the present issue [24] verified that this specific relationship holds true in both demented PD patients and patients with Alzheimer's disease. Actually, Grossi et al [24] explored memory, visuospatial and executive functions in patients affected by the two neurodegenerative diseases; the authors also used specific behavioral rating scales and an inventory developed to measure severity of apathy on clinical basis, the newly proposed Clinical Judgment for Apathy Syndrome. The results showed that apathetic patients with both forms of dementia showed a common neuropsychological and behavioral picture, characterized by impairment on frontal tasks, thus strongly supporting the existence of an 'apathetic syndrome', characterized by specific cognitive and psychological symptoms.…”
supporting
confidence: 56%
“…This hypothesis about the neural bases of apathy received support from neuropsychological studies highlighting the presence of frontal/executive disorders in PD patients with "pure apathy" (i.e., non-demented, non-depressed patients with high scores on specific questionnaires for apathy) [22,23]. An original research paper by Grossi et al in the present issue [24] verified that this specific relationship holds true in both demented PD patients and patients with Alzheimer's disease. Actually, Grossi et al [24] explored memory, visuospatial and executive functions in patients affected by the two neurodegenerative diseases; the authors also used specific behavioral rating scales and an inventory developed to measure severity of apathy on clinical basis, the newly proposed Clinical Judgment for Apathy Syndrome.…”
mentioning
confidence: 53%